The chaperone Chs7 forms a stable complex with Chs3 and promotes its activity at the cell surface. (4th March 2018) - Dharwada, Sai T.; Dalton, Lauren E.; Bean, Björn D. M.; Padmanabhan, Nirmala; Choi, Catherine; Schluter, Cayetana; Davey, Michael; Conibear, Elizabeth
Abstract : The polytopic yeast protein Chs3 (chitin synthase III) relies on a dedicated membrane‐localized chaperone, Chs7, for its folding and expression at the cell surface. In the absence of Chs7, Chs3 forms high molecular weight aggregates and is retained in the endoplasmic reticulum (ER). Chs7 was reported to be an ER resident protein, but its role in Chs3 folding and transport was not well characterized. Here, we show that Chs7 itself exits the ER and localizes with Chs3 at the bud neck and intracellular compartments. We identified mutations in the Chs7 C‐terminal cytosolic domain that do not affect its chaperone function, but cause it to dissociate from Chs3 at a post‐ER transport step. Mutations that prevent the continued association of Chs7 with Chs3 do not block delivery of Chs3 to the cell surface, but dramatically reduce its catalytic activity. This suggests that Chs7 engages in functionally distinct interactions with Chs3 to first promote its folding and ER exit, and subsequently to regulate its activity at the plasma membrane. Abstract : Chs7 is reported to be a dedicated endoplasmic reticulum (ER) chaperone required for Chs3 folding. In this study, we show that Chs7 exits the ER with Chs3 and accompanies it to the cell surface, where it is required for chitin synthase activity. We propose that Chs7 is not only required for Chs3 folding at the ER, but has an additional role in regulating Chs3 trafficking and activity at the cell surface.